Low Complexity Iterative Receiver Design for Shallow Water Acoustic Channels. (22nd March 2010) - Shah Shah, C. P. C. P.; Tsimenidis Tsimenidis, C. C. C. C.; Sharif Sharif, B. S. B. S.; Neasham Neasham, J. A. J. A.
Abstract : An adaptive iterative receiver structure for the shallow underwater acoustic channel (UAC) is proposed using a decision feedback equalizer (DFE) and employing bit-interleaved coded modulation with iterative decoding (BICM-ID) in conjunction with adaptive Doppler compensation. Experimental results obtained from a sea trial demonstrate that the proposed receiver not only reduces inherent problem of error propagation in the DFE but also improves its convergence, carrier phase tracking, and Doppler estimation. Furthermore, simulation results are carried out on UAC, modelled by utilizing geometrical modelling of the water column that exhibits Rician statistics and a long multipath spread resulting in severe frequency selective fading and intersymbol interference (ISI). It has been demonstrated that there is a practical limit on the number of feedback taps that can be employed in the DFE and data recovery is possible even in cases where the channel impulse response (CIR) is longer than the span of the DFE. The performance of the proposed receiver is approximately within 1 dB of a similar system employing DFE and turbo code, however, at a significantly reduced computational complexity and memory requirements, making our system attractive for real-time implementation.